# Discussion Session 9: Unification¶

## Statement of Problem¶

Unification, in computer science and logic, is an algorithmic process of solving equations between symbolic expressions. [1]

term    ::=  variable
term    ::=  id (termlst)
termlst ::=  term termlst
termlst ::=


Substitution is a mapping from id to term.

The essential task of unification is to find a substitution $$\sigma$$ that unifies two given terms (i.e., makes them equal). Let’s write $$\sigma (t)$$ for the result of applying the substitution $$\sigma$$ to the term $$t$$. Thus, given $$t_1$$ and $$t_2$$, we want to find $$\sigma$$ such that $$\sigma(t_1) = \sigma(t_2)$$. Such a substitution $$\sigma$$ is called a unifier for $$t_1$$ and $$t_2$$. For example, given the two terms:

f(x, g(y))      f(g(z), w)


where x, y, z, and w are variables, the substitution:

sigma = {x: g(z), w: g(y)}


would be a unifier, since:

sigma( f(x, g(y)) ) = sigma( f(g(z), w) ) = f(g(z), g(y))


Unifiers do not necessary exist. However, when a unifier exists, there is a most general unifier (mgu) that is unique up to renaming. A unifier $$\sigma$$ for $$t_1$$ and $$t_2$$ is an mgu for $$t_1$$ and $$t_2$$ if

• $$\sigma$$ is a unifier for $$t_1$$ and $$t_2$$; and
• any other unifier $$\sigma'$$ for $$t_1$$ and $$t_2$$ is a refinement of $$\sigma$$; that is, $$\sigma'$$ can be obtained from $$\sigma$$ by doing further substitutions.

## Application of Unification¶

• Pattern Matching (A simplified version of Unification)

Algorithm and example (notes)

• Type Inference

Let’s set up some typing rules for Python similar to those of Java or C. Then we can use unification to infer the types of the following Python programs:

def foo(x):
y = foo(3)
return y

def foo(x):
y = foo(3)
z = foo(y)
return z

def foo(x):
y = foo(3)
z = foo(4)
r = foo(y, z)
return r

• Logic Programming (Prolog)

## A More General Unification Algorithm¶

Some examples that simplified algorithm cannot handle:

x     f(x)
f(x, g(x))     f(h(y), y)


Instead of unifying a pair of terms, we work on a list of pairs of terms:

# We use a list of pairs to represent unifier. The unifier has a property
# no variable on a lhs occurs in any term earlier in the list
# [(x3: x4), (x1: f(x3, x4)), (x2: f(g(x1, x3), x3))]
# Another way to view this.
# Let's rename these variables by ordering them.
# x3 -> y1
# x4 -> y0
# x1 -> y2
# x2 -> y3
# [(y1: y0), (y2: f(y1, y0)), (y3: f(g(y2, y1), y1))]

def unify_one(t1, t2): # return a list of pairs for unifier
if t1 is variable x and t2 is variable y:
if x == y:
return []
else:
return [(x, t2)]
elif t1 is f(ts1) and t2 is g(ts2): # ts1 and ts2 are lists of terms.
if f == g and len(ts1) == len(ts2):
return unify(ts1, ts2)
else:
return None # Not unifiable: id conflict
elif t1 is variable x and t2 is f(ts):
if x occurrs in t2:
return None # Not unifiable: circularity
else:
return [(x, t2)]
else: # t1 is f(ts) and t2 is variable x
if x occurrs in t1:
return None # Not unifiable: circularity
else:
return [(x, t1)]

def unify(ts1, ts2): # return a list of pairs for unifier
if len(ts1) == 0:
return []
else:
ts1_tail = ts1[1:]
ts1_tail = ts2[1:]

s2 = unify(ts1_tail, ts2_tail)
s1 = unify_one(t1, t2)
return s1 + s2

def apply(s, t):
// substitute one by one backward
n = len(s) - 1
while n >= 0:
p = s[n]
t = subs(p, t)
n = n - 1
return t


Example:

f(x1, g(x2, x1), x2)    f(a, x3, f(x1, b))